Pengembangan e-Modul Berbasis Studi Kasus pada Materi Sistem Saraf untuk Siswa SMA Kelas XI - Richa Amalia; Afreni Hamidah; Dara Mutiara Aswan; Jodion Siburian (Jurnal Penelitian Pendidikan IPA, 2025)
The nervous system is a complex biological because the material is still abstract. The method used by teachers is the lecture method which causes students to have difficulty in understanding the material. To overcome this, a case study-based e-Module is needed that can provide students with cases related to the material and be a solution to students' difficulties related to minimal learning in class. This study aims to develop a case study-based e-Module on the nervous system material and analyze the feasibility of the developed product. This study uses the ADDIE development model consisting of Analyze, Design, Develop, Implement and Evaluation. The results of the study showed that the developed e-Module obtained a percentage of 91.66% with the category "very feasible" in the material validation. At the media validation stage, a percentage value of 94.11% was obtained with the category "very feasible". The biology teacher's perception of the quality of the developed product obtained a percentage of 91.17% with the category "very good". Small group trials with students obtained a percentage of 95.20% with the category "very good" and large group trials obtained a percentage of 94.68% with the category "very good". Thus, it can be concluded that the product developed is feasible and practical and received by teachers and students as a learning tool that supports students' learning process on the nervous system material.